The Role of Gender Diversity on Debt Policy - Evita Fardi Kusuma Dewi (Green Publisher Indonesia, 2024)
This study aims to evaluate the effect of gender diversity in the board of directors on debt policy in the Indonesian banking sector. Using balanced panel data analysis, this study examines the impact of gender diversity, firm size, profitability, and current ratio on debt policy. The results show that gender diversity does not have a significant influence on debt policy. Meanwhile, firm size is shown to have a positive influence, and profitability has a negative influence on debt policy. The current ratio does not show a significant influence. This study contributes to the existing literature by highlighting the factors that influence debt policy in the banking sector, particularly in the context of a modernizing economy and gender diversity in debt policy decision-making. It also provides a reference for other academic studies exploring the relationship between board gender diversity, capital structure, financial performance, and corporate governance across different industries and regions.